Penerapan Pengelolaan Keuangan Berkelanjutan Dalam Meningkatkan Daya Saing PT Widodo Makmur Unggas Tbk - Sarah Fina Sarah; Sany Putri Dorojatun; Selvi Irene Claudia (CV. ITTC INDONESIA, 2025)
This study aims to examine how the implementation of sustainable financial management can enhance the competitiveness of a company, specifically PT Widodo Makmur Unggas Tbk. In the era of green economy and sustainable growth, companies are expected to focus not only on profitability but also on social and environmental responsibility. Using a qualitative descriptive approach, data were collected from financial reports, corporate policy documents, and interviews with management and other stakeholders. The results indicate that integrating sustainability aspects into financial strategies—such as investing in energy efficiency, waste management, and transparent ESG (Environmental, Social, Governance) reporting—has a positive impact on corporate image and investor trust. Therefore, sustainable financial management significantly contributes to strengthening PT Widodo Makmur Unggas Tbk’s competitiveness in both domestic and international markets.